Onset of Alveolization Processes in Sandstones Exposed to Salt Weathering - Marco Ludovico-Marques; Carlos Chastre (Buildings, 2024)
Sandstones of the Lourinhã Formation were studied. Alveolization is the major form of weathering on the façades of monuments near Peniche in the western region of Portugal. Salt weathering is an important cause of this degradation form. Stones of specimens, similar to those found in these ancient buildings, were used for an experimental program of artificial salt ageing through the use of sodium chloride, calcium chloride, and sodium sulfate solutions, all at 10% (w/w). Salt weathering follow-up was carried out viz. the assessment of the degradation effect on these specimens of lower values of porosity under crystallization–dissolution cycles. Sodium chloride and sodium chloride with calcium sulfate were the more deleterious solutions, causing failure of the specimens after at least 40 cycles of immersion/drying. Surfaces of the sandstone specimens of variety A showed the onset of the alveolization form due to the use of a saline solution of sodium chloride with calcium sulfate.